156k views
0 votes
4) -6x + 5y = 1
6x + 4y=-10

User Gardezi
by
4.7k points

2 Answers

1 vote

Answer:

x = - 1, y = - 1

Explanation:

- 6x + 5y = 1 (1)

6x + 4y = - 10 (2)

Add (1) to (2) sides by sides

9y=-9

Dividing both sides by 9

y = -1

Substitute y = -1 into equation (2)

6x + 4(-1) = - 10

6x = -6

x = - 1

User Jiffyclub
by
4.6k points
2 votes
so x would equal -1 and y would equal -1. also, incase you needed to know I used the substitution method to solve. hope this helps :)
4) -6x + 5y = 1 6x + 4y=-10-example-1
User Andreofthecape
by
4.6k points